Osteotomies: Advanced and complex techniques - Clarke,S; Cobb,J; Jaere,M; Jones,G; Kley,K; Lobenhoffer,P; McCrum,C; Musahl,V; Takeuchi,R (2018)
We started performing precise surgery based upon CT plans in the last century - the first embodiment of this approach was a robotic assistant built for total knee replacement, the “Acrobot” [1]. Abundant evidence now exists to confirm that assistive technologies enable surgeons to achieve their preoperative goals [2]. The concept of planned surgery is therefore not novel. Patient-matched instruments share several key elements with the robotic platform, and these formed the basis of this current project. The essential elements include image segmentation, planning, and registration. We applied the know-how of these dimensions to design and build patient-matched guides for a range of tasks using biocompatible polymer 3D printers. Having established a workflow for arthroplasty, the adaptation of the same principles to osteotomy was a short step, requiring software to be developed to deliver semiautomated useful information regarding limb segment alignment and the shapes of bones.